EXPERIENTIAL FUNCTION USED BY TUMOING, THE MAIN CHARACTER IN SI TUMOING MANGGORGA ARI SOGOT NOVEL - Octaviani Hutabalian; Zainuddin (State University of Medan, 2018)
The study investigates the aplication of Halliday’s theory of experiential function into Batak Toba clauses and to identify the types of experiential functions and the manners in which experiential functions are used by Tumoing in Saut Poltak Tambunan’s novel “Si Tumoing Manggorga Ari Sogot”. The study was conducted to describe type of process, participants function and circumstatial elements of experiential function in the novel. The study applied descriptive qualitative method. The data were taken from the utterances produced by the main character. The finding showed there were 6 types of processes, 14 types of participants and 8 circumtances in the dialogues of Tumoing. The dominant type of process was Relational process (35,70 %) while Actor as the dominant type of participant (13, 42 %) and Location as the dominant type of circumtance (48,70 %). The findings also showed that the main character was honest person and friendly person. It’s explained by the relational process i.e using atributing and identifying.